Effect of ecoregion and river type on neotropical Chironomidae (Diptera) from humid mountain to semiarid lowland: Chironomidae from Yungas and Chaco - Pero, Edgardo Javier Ignacio; Torrejón, Silvia Elena; Molineri, Carlos (Revista de Biología Tropical, 2023)
Introduction: Chironomidae (Diptera) is the most widespread and abundant aquatic insect family in freshwater ecosystems. Chironomids are considered good indicators of water quality but are seldom identified at the genus level in broad spatial scale studies. Objective: To identify environmental conditions associated with chironomids in an altitudinal gradient. Methods: We compared ecoregions, river types, and seasons, for chironomids in neotropical streams and rivers (18 river sites; 2014-2018; Yungas rainforest and Western Chaco dry forest, Argentina). We used non-metric multidimensional scaling, dissimilarity, envfit analysis and rank-abundance curves. Results: Chironomic “assemblages” matched both ecoregions and river types. However, ecoregions presented a better fit with species composition. The stenothermal taxa of Orthocladiinae were dominant at high elevations and the eurythermal Chironominae in lowland rivers. Altitude, water temperature and conductivity were important. Seasonal differences were smaller than ecoregional differences. Conclusions: Ecoregions, altitude, water temperature and conductivity correlated with chironomid communities. Orthocladiinae were dominant at high elevations and Chironominae in lowland rivers.